2021
DOI: 10.3390/cancers13164169
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk Factor for Prostate Cancer Mortality: A Systematic Review and Dose-Response Meta-Analysis of 280,199 Patients

Abstract: The aim of this study was to systematically review all evidence evaluating obesity as a prognostic factor for PC mortality. Cohort and case-control studies reporting mortality among PC patients stratified by body mass index (BMI) were included. The risk of mortality among obese patients (BMI ≥ 30) was compared with the risk for normal weight (BMI < 25) patients, pooling individual hazard ratios (HR) in random-effects meta-analyses. Reasons for heterogeneity were assessed in subgroup analyses. Dose-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 79 publications
1
17
0
1
Order By: Relevance
“…Additionally, a recent meta-analysis, published in JAMA in 2021, showed that obesity (BMI ≥ 30) resulted in a 17% increase in cancer specific mortality compared to non-obese (BMI < 30) people (HR = 1.17 [1.12-1.23]) [34] (Table 1). In addition, several other meta-analyses have shown that obesity is associated with cancer mortality in a wide range of disease sites, such as prostate, breast, pancreas, and liver cancers [56][57][58][59], with many of these studies demonstrating a consistent dose response per increase in BMI [56][57][58][59][60]. Using the NEJM paper as an example, for roughly every 62 people who decrease their BMI from ≥30 to ≤24.9, and for every 130 people who decrease their BMI from 25-29.9 to ≤24.9, one cancer death would be prevented.…”
Section: Obesitymentioning
confidence: 99%
“…Additionally, a recent meta-analysis, published in JAMA in 2021, showed that obesity (BMI ≥ 30) resulted in a 17% increase in cancer specific mortality compared to non-obese (BMI < 30) people (HR = 1.17 [1.12-1.23]) [34] (Table 1). In addition, several other meta-analyses have shown that obesity is associated with cancer mortality in a wide range of disease sites, such as prostate, breast, pancreas, and liver cancers [56][57][58][59], with many of these studies demonstrating a consistent dose response per increase in BMI [56][57][58][59][60]. Using the NEJM paper as an example, for roughly every 62 people who decrease their BMI from ≥30 to ≤24.9, and for every 130 people who decrease their BMI from 25-29.9 to ≤24.9, one cancer death would be prevented.…”
Section: Obesitymentioning
confidence: 99%
“…Prostate volume is widely known to be correlated positively with PSA blood levels and to not be a causal factor for PCa. The relationship between BMI (BMI: weight/height 2 ) and PCa risk or aggressiveness has been the subject of contradictory reports across over 1000 publications over the last 10 years [22,23]. Recent results using Mendelian randomization approaches suggest that height increases risk of PCa, whereas BMI decreases this risk [21].…”
Section: Family History Bmi Height and Prostate Volume And Associatio...mentioning
confidence: 99%
“…11 Notably, obesity has been recognized to have a role in PCa development, progression, and death, although results were inconsistent. [12][13][14][15][16][17] Obese men with PCa are suggested to be at higher risk of a more aggressive tumor phenotype, advanced disease at diagnosis, and poorer treatment outcomes. 12,14 Several mechanisms may be responsible for these higher risk factors, including increased systemic inflammation, hyperinsulinemia, metabolic abnormalities associated with fat mass, and changes in the adipokine profile.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, obesity has been recognized to have a role in PCa development, progression, and death, although results were inconsistent 12–17 . Obese men with PCa are suggested to be at higher risk of a more aggressive tumor phenotype, advanced disease at diagnosis, and poorer treatment outcomes 12,14 .…”
Section: Introductionmentioning
confidence: 99%